A Turkish Version of the School Social Behavior Scales (SSBS) - (:unkn) unknown (EDAM, 2009)
Intended to enhance social skills instruction in Turkey, the present study highlights the process and outcome of creating a Turkish-language version of the School Social Behavior Scales (SSBS), originally developed by Merrell (1993). The social skills of the Turkish pre-and elementary school students were based on the Likert scale. The analyses of the data obtained from 467 students and their teachers were carried out on the linguistic equivalency, item-total and item-remainder analyses, confirmatory factor analyses, criterion validity, and reliability analyses of the Turkish conversion of the SSBS. The results of the analyses of linguistic equivalency reflected significance for each item of p<.001. A level of significance of p<.001 was found by means of the item-total, item-remainder, and discrimination analyses. Reliability values ranging between r=.91 and r=.98 were obtained by the Cronbach coefficient alpha, Spearman Brown, and Guttman Split-Half techniques. These reliability coefficients display a similarity with those for the original version. The data obtained by means of the Matson Evaluation of Social Skills with Youngsters (MESSY) and sociometric technique were evaluated and found to bear statistical significance (p < .05). Based on the findings, it may be stated that the Turkish conversion of the SSBS may be used with Turkish samples and that it is a valid and reliable measurement tool.
Keywords: Social Skills; Social Competence; Antisocial Behavior; SKILLS; DIMENSIONS; TEACHER